El posmodernismo: un apagón cultural histórico (2008)
ABSTRACT: The posmodernismo is the intellectual fashion of the present time. The great dreams collapsed. The socialism, instead of being fruit of the childbirth of an exhausted and dying society, constituted the abortion of a global society. Of the heroic revolutions it is not nothing. Capitalism lacks alternative today. Sufficient reason like for a strong collective depression and factor of frustration.